2017
DOI: 10.1016/j.copsyc.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Do you wish to waive your rights? Affect and decision-making in multilingual speakers

Abstract: This paper reviews recent developments in the study of multilingualism and affect, with the focus on two active areas: affective processing and decision-making. The converging pattern of findings suggests that foreign (FL) and second language (L2) processing do not engage affect to the same extent as processing in the first language (L1). This decreased reliance on affect has been linked to the systematic finding that speakers dealing with moral dilemmas and financial scenarios in a foreign language are less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 40 publications
4
42
0
1
Order By: Relevance
“…Some studies on bilingualism and emotions (e.g., Harris et al, 2003; Harris, 2004; Caldwell-Harris, 2015; Hsu et al, 2015) have also suggested that L2 emotional words evoke less autonomic physiological response than L1 words, leading some authors to describe L2 as “disembodied” (for a review see Pavlenko, 2012, 2017). However, as Sheikh and Titone (2013) have pointed out, there might be a difference between emotionally grounded and sensorimotor grounded concepts, difference which goes beyond the scope of this paper.…”
Section: Studies On L2 Embodied Semantic In Healthy Populationsmentioning
confidence: 99%
“…Some studies on bilingualism and emotions (e.g., Harris et al, 2003; Harris, 2004; Caldwell-Harris, 2015; Hsu et al, 2015) have also suggested that L2 emotional words evoke less autonomic physiological response than L1 words, leading some authors to describe L2 as “disembodied” (for a review see Pavlenko, 2012, 2017). However, as Sheikh and Titone (2013) have pointed out, there might be a difference between emotionally grounded and sensorimotor grounded concepts, difference which goes beyond the scope of this paper.…”
Section: Studies On L2 Embodied Semantic In Healthy Populationsmentioning
confidence: 99%
“…We claim that the use of a foreign language—that is, a language that has been learned in a classroom context rather than by immersion in a culture (Pavlenko, 2012)—helps achieve this. We base our claim on prior research showing that when people use a foreign language, their intuitive system is less alert, less swift to recognise that something is good or bad (see Hadjichristidis, Geipel, & Surian, 2017; for reviews on how foreign language use affects judgement and decision-making, see Caldwell-Harris, 2015; Costa, Vives, & Corey, 2017; Hayakawa, Costa, Foucart, & Keysar, 2016; Pavlenko, 2017). For example, people discuss longer about embarrassing topics (Bond & Lai, 1986) and are less reluctant to use swearwords (Dewaele, 2004).…”
mentioning
confidence: 99%
“…These findings imply for example a modulation of unpleasant-word processing by subclinical depression and anxiety, as well as possible prefrontal compensatory processes during unintentional emotion regulation in subjects with higher trait anxiety [ 30 ]. Notably, word stimuli are easy to apply, and isolated unpleasant words are typically less disturbing than their pictorial counterparts, although responses induced by words in non-native speakers need to be regarded with caution [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%